1992
DOI: 10.1200/jco.1992.10.8.1317
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of clinicopathologic staging for localized soft tissue sarcoma of the extremity: a study of 423 adults.

Abstract: The refinement of clinicopathologic staging may depend on the choice of outcome variable: ultimate prognosis versus early metastatic spread. Additionally, the observed local recurrence effect may be explained by a tendency for some patients to acquire one or more unfavorable risk factors at the time of local recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
95
3
5

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(115 citation statements)
references
References 79 publications
12
95
3
5
Order By: Relevance
“…This concept is also supported by the large difference between patients with and without local recurrence in the interval between primary treatment and metastases. Hence, among patients with small and/or low-grade tumors, local recurrence was a significant risk factor, a finding which is in agreement with a similar study from the Memorial Sloan-Kettering Cancer Center (Gaynor et al 1992).…”
Section: Discussionsupporting
confidence: 80%
“…This concept is also supported by the large difference between patients with and without local recurrence in the interval between primary treatment and metastases. Hence, among patients with small and/or low-grade tumors, local recurrence was a significant risk factor, a finding which is in agreement with a similar study from the Memorial Sloan-Kettering Cancer Center (Gaynor et al 1992).…”
Section: Discussionsupporting
confidence: 80%
“…Recent independent studies of a large series of soft tissue sarcomas showed that histologic tumour grade, tumour depth and tumour size were independent prognostic factors (Gaynor et al, 1992;Coindre et al, 1996). In the current study, Cox proportional hazard multivariate analysis revealed that histologic grade was the most valuable independent prognostic factor in patients with soft tissue sarcoma.…”
Section: Discussionsupporting
confidence: 51%
“…Recent studies on a large number of soft tissue sarcoma cases have claimed that the grade of the tumour, size of the tumour and tumour depth are independent prognostic factors (Gaynor et al, 1992;Coindre et al, 1996). There is a general consensus that the size of tumour tissue is an important and easily obtainable parameter of tumour growth and that the growth of tumour is largely dependent on neovascularity in solid tumours.…”
mentioning
confidence: 99%
“…Several analyses of prognostic factors influencing both local recurrence and overall survival in patients with extremity soft tissue sarcomas show tumor stage, grade, size, depth, and anatomic site are most important for patient survival [6,13,24,26]. Negative surgical margin, low histologic grade, and use of radiotherapy are the most important factors in achieving local disease control [6,8,10,12,23,27,30,33].…”
Section: Introductionmentioning
confidence: 99%